2013
DOI: 10.1093/plankt/fbt100
|View full text |Cite
|
Sign up to set email alerts
|

A metabolic approach to dormancy in pelagic copepods helps explaining inter- and intra-specific variability in life-history strategies

Abstract: Dormancy (diapause) is a key life-history strategy of pelagic copepods that allows them to thrive in highly seasonal environments. Successful dormancy of copepodid stages requires the ability to store energy efficiently (for example as lipids) and to slow down the rate of mobilization of this capital during the dormant period. The physiology of lipids in copepods has been extensively reviewed; however, data about the energetics of dormancy are currently scattered throughout the literature. Thus, we conducted a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
58
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(61 citation statements)
references
References 50 publications
3
58
0
Order By: Relevance
“…Merging Coltrane 1.0 with a light-and size-based predation scheme similar to Varpe et al (2015) or Ohman and Romagnan (2015) would allow one to better test the balance of bottom-up and top-down controls on calanoid biogeography. Second, our experience constructing the Bering Sea and Disko Bay cases suggests that the greatest uncertainty in the model bioenergetics is actually not the physiology itselfempirical reviews like Saiz and Calbet (2007), Maps et al (2014), Kiørboe and Hirst (2014), and have constrained the key rates moderately well-but rather the problem of translating a prey field into a rate of ingestion. Within each of our model testbeds, the prey time series P remains subject to uncertainty in relative grazing rates on ice algae, large and small pelagic phytoplankton, and microzooplankton, despite a wealth of local observations and a history of work on this problem in Calanus specifically (Olson et al, 2006;Campbell et al, 2009, in press).…”
Section: Uncertainties and Unresolved Processesmentioning
confidence: 99%
“…Merging Coltrane 1.0 with a light-and size-based predation scheme similar to Varpe et al (2015) or Ohman and Romagnan (2015) would allow one to better test the balance of bottom-up and top-down controls on calanoid biogeography. Second, our experience constructing the Bering Sea and Disko Bay cases suggests that the greatest uncertainty in the model bioenergetics is actually not the physiology itselfempirical reviews like Saiz and Calbet (2007), Maps et al (2014), Kiørboe and Hirst (2014), and have constrained the key rates moderately well-but rather the problem of translating a prey field into a rate of ingestion. Within each of our model testbeds, the prey time series P remains subject to uncertainty in relative grazing rates on ice algae, large and small pelagic phytoplankton, and microzooplankton, despite a wealth of local observations and a history of work on this problem in Calanus specifically (Olson et al, 2006;Campbell et al, 2009, in press).…”
Section: Uncertainties and Unresolved Processesmentioning
confidence: 99%
“…Recently, Maps et al (2014) summarised published metabolic rates for Calanus species. In total, five papers have reported respiration rates for C. finmarchicus (Hirche, 1983;Marshall and Orr, 1958;Saumweber and Durbin, 2006;Ingvarsdóttir et al, 1999;Ikeda et al, 2001).…”
Section: Metabolism and Excretionmentioning
confidence: 99%
“…finmarchicus and C. helgolandicus should be very similar. In addition, Maps et al (2014) concluded that there was an almost identical inter-species pattern in allometric scaling of metabolism with body size across Calanus species. However, apparent interspecies differences in response of ingestion to temperature suggests that the energetics of each species differ, which may result in different metabolic rates.…”
Section: Metabolism and Excretionmentioning
confidence: 99%
See 2 more Smart Citations